Bookleggers and smuthounds : the trade in erotica, 1920-1940 - Gertzman, Jay A. (University of Pennsylvania Press ; University Presses Marketing [distributor], 2002)
Between the two world wars, at a time when both sexual repression and sexual curiosity were commonplace, New York was the center of the erotic literature trade in America. The market was large and contested, encompassing not just what might today be considered pornographic material but also sexually explicit fiction of authors such as James Joyce, Theodore Dreiser, and D.H. Lawrence; mail-order manuals; pulp romances; and "little dirty comics."Bookleggers and Smuthoundsvividly brings to life this significant chapter in American publishing history, revealing the subtle, symbiotic relationship between the publishers of erotica and the moralists who attached themand how the existence of both groups depended on the enduring appeal of prurience. By keeping intact the association of sex with obscenity and shameful silence, distributors of erotica simultaneously provided the antivice crusaders with a public enemy. Jay Gertzman offers unforgettable portrayals of the "pariah capitalists" who shaped the industry, and of the individuals, organizations, and government agencies that sought to control them. Among the most compelling personalities we meet are the notorious publisher Samuel Roth, "the Prometheus of the Unprintable," and his nemesis, John Sumner, head of the New York Society for the Suppression of Vice, a man aggressive in his pursuit of pornographers and in his quest for a morally unitedand ethnically homogeneousAmerica.